Zika virus infection in human placental tissue explants is enhanced in the presence of dengue virus antibodies in-vitro - Kyra Hermanns; Claudia Göhner; Anne Kopp; Andre Schmidt; Waltraut M. Merz; Udo R. Markert; Sandra Junglen; Christian Drosten (Emerging Microbes and Infections, 2018)
Abstract The current Zika virus (ZIKV) outbreak is associated with neurological malformations and disorders in neonates. Areas of increased incidence of malformations may overlap with dengue-hyperendemic areas. ZIKV infection is enhanced by antibodies against dengue virus (DENV) in cell culture and inbred mice. Sufficiently powered clinical studies or primate studies addressing the enhancement of fetal ZIKV infection after previous dengue infection are not available. The human placenta is susceptible to ZIKV in vitro, but it is unknown whether antibody-dependent enhancement of ZIKV infection occurs at the placental barrier. Here we studied ZIKV infection in placental tissue in the presence of DENV-immune sera. Explants from the amniochorionic membrane, the chorionic villi, and the maternal decidua were infected with ZIKV in the presence of DENV type 1-, 2-, or 4-immune sera, or controls. Presence of DENV antibodies of any type enhanced the percentage of successful infections of organ explants between 1.42- and 2.67-fold, and led to a faster replication as well as significantly increased virus production. No enhancement was seen with yellow fever or chikungunya virus control sera. Pre-existing DENV antibodies may pose an increased risk of trans-placental ZIKV transmission.